PROBLEM RELASI FILSAFAT PENDIDIKAN ISLAM DAN UMUM - Almi Novita; Abdul Mukit (AL - IBRAH, 2023)
This research investigates the differences and similarities between educational philosophy and Islamic educational philosophy. Western educational philosophy tends to derive from the boundless rationality of human thinking, raising doubts due to its limitations on human reason and separating religion from scientific knowledge (Anthropocentric). On the other hand, Islamic educational philosophy is grounded in the concept of God (Theocentric), with goals closely related to the teachings of the Quran and Sunnah, eliminating doubts through faith and revelation. Despite fundamental differences, this study also highlights the similarities between the two philosophies. Both are conceptual frameworks for thinking about education, and specific theories converge. Nativism, Empiricism, and Convergence Theory serve as meeting points between educational philosophy and Islamic educational philosophy. This study will discuss the practical implications of these differences and similarities in the context of modern education, exploring the potential integration of Western and Islamic thought in designing holistic and balanced learning strategies. The results of this research are expected to provide profound insights into how the approaches of educational philosophy and Islamic educational philosophy can positively contribute to the formation of an inclusive and holistic educational paradigm.